Couples' Subjective Well-Being Around Live Birth and Pregnancy Loss - Alessandro Di Nallo (Population and Development Review, 2025)
This study examines the trajectories of subjective well-being (SWB) of women and their partners transitioning to parenthood or remaining childless after experiencing pregnancy loss~in the United Kingdom. Childbearing is generally associated with short-term improvements in women's and men's SWB. However, less is known about couples' well-being dynamics before and after pregnancies ending in losses, despite 10–20 percent of the pregnancies that occurred in high-income countries terminating spontaneously. Using fixed-effects linear regressions, the study analyses first-time pregnancies of women recorded across the 13 waves of the UK Household Longitudinal Study (UKHLS), from 2009 to 2023 ( N ~=~18,897 observations for women and N ~=~11,223 for men). The results indicate that there are differences in SWB trajectories based on pregnancy outcomes, with mothers showing better SWB compared to women who experience pregnancy loss. The involuntary terminations negatively impact two indicators of women's SWB (mental health and life satisfaction) upon pregnancy loss, while women who had a live birth experience an increase in SWB around childbearing. Partners are less affected by pregnancy loss, though the effects on life satisfaction scores may be more persistent. These results suggest that the well-being consequences of pregnancy loss are primarily, but not exclusively, shouldered by women.
Keywords: 300; mental health; pregnancy loss; live birth; couples; fixed effects; longitudinal data; United Kingdom